Control of Uterine Microenvironment by Foxp3+ Cells Facilitates Embryo Implantation - Teles, Ana; Schumacher, Anne; Kühnle, Marie C.; Linzke, Nadja; Thuere, Catharina; Reichardt, Peter; Tadokoro, Carlos E.; Hämmerling, Günter J.; Zenclussen, Ana C. (Frontiers in Immunology, 2013)
Implantation of the fertilized egg into the maternal uterus depends on the fine balance between inflammatory and anti-inflammatory processes. Whilst regulatory T cells (Tregs) are reportedly involved in protection of allogeneic fetuses against rejection by the maternal immune system, their role for pregnancy to establish, e.g. blastocyst implantation, is not clear. By using 2-photon imaging we show that Foxp3+ cells accumulated in the mouse uterus during the receptive phase of the oestrus cycle. Seminal fluid further fostered Treg expansion. Depletion of Tregs in two Foxp3.DTR-based models prior to pairing drastically impaired implantation and resulted in infiltration of activated T effector cells as well as in uterine inflammation and fibrosis in both allogeneic and syngeneic mating combinations. Genetic deletion of the homing receptor CCR7 interfered with accumulation of Tregs in the uterus and implantation indicating that homing of Tregs to the uterus was mediated by CCR7. Our results demonstrate that Tregs play a critical role in embryo implantation by preventing the development of a hostile uterine microenvironment.